Pengaruh Range Of Motion (ROM) Angkle Terhadap Resiko Deep Vein Thrombosis (DVT) Pada Pasien Diabetes Mellitus Dengan Luka Ulkus: Literature Review - Ayu, Yennyka Dwi; Dewi, Arlina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Background: Diabetes Mellitus (DM) is the most chronic disease throughout the world which is a chronic metabolic disease due to pancreas that cannot produce enough insulin and the body cannot use effective insulin, as evidenced by the number of diabetes mellitus prevalence that can continue at any time increased. Diabetes mellitus is a metabolic disease which is very high risk of death. Patients with diabetes mellitus participate with thrombosis in blood vessels, one of which is diabetic foot ulcer. Thrombosis in patients with diabetic foot ulcers will increase thrombosis in the lower limbs that are part of venous thromboembolism, or Deep Vein Thrombosis (DVT). One effort to repair the wound can be done with practice. Exercise is one of the first management strategies proposed for new patients diagnosed with diabetes, because along with diet and policy modifications, exercise and exercise are important components of all diabetes intervention programs, which by doing exercises can help very much.Research Objectives: This literature review discusses the causes of deep venous thrombosis (DVT), causes of ulcer wounds and looks for the influence of the Angkle range of motion (ROM) on the risk of Deep Vein Thromosis (DVT) in patients with diabetes mellitus with ulcer wounds.Method: The literature database search method was conducted at Google Scholar and Pubmed. The literature used is literature that meets the inclusion criteria and published the last five years, is approved then selected and reviewed.Results: Final results There are 4 literatures that can be reviewed. Based on the literature conclusions, it can be found several exercises in patients with diabetes mellitus so as to increase diabetes, and can reduce the need for Deep Vein Thromosis (DVT). To find out the risk of Deep Vein thrombosis (DVT) can be determined by the D-Dimer test. If the D-Dimer test shows positive results, then the patient must use DVT